Regulatory interplay between TFIID’s conformational transitions and its modular interaction with core promoter DNA - Cianfrocco, Michael A (Landes Bioscience, 2013)
Recent structural and biochemical studies of human TFIID have significantly increased our understanding of the mechanisms underlying the recruitment of TFIID to promoter DNA and its role in transcription initiation. Structural studies using cryo-EM revealed that modular interactions underlie TFIID’s ability to bind simultaneously multiple promoter motifs and to define a DNA state that will facilitate transcription initiation. Here we propose a general model of promoter binding by TFIID, where co-activators, activators, and histone modifications promote and/or stabilize a conformational state of TFIID that results in core promoter engagement. Within this high affinity conformation, we propose that TFIID’s extensive interaction with promoter DNA leads to topological changes in the DNA that facilitate the eventual loading of RNAP II. While more work is required to dissect the individual contributions of activators and repressors to TFIID’s DNA binding, the recent cryo-EM studies provide a physical framework to guide future structural, biophysical, and biochemical experiments.